ACCEPTANCE OF COVID-19 VACCINATION AMONG STUDENTS OF HEALTH SCIENCES CHITTOOR ANDHRA PRADESH INDIA - JEERAGYAL, DEVIKA P; DEVENDRA BASTI, BHARATESH; B, SRINIVASA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: To understand the overall perception of acceptance of COVID-19 vaccination if it is given free of cost by the Government of India. Methods: A cross-sectional study was done at Apollo Medical College in Chittoor district, Andhra Pradesh. A study was undertaken among students of different courses, like medical students, nursing students, physiotherapy students, and medical skill students, who are currently studying in this college. After getting written informed consent, a pretested questionnaire was used to collect the data. Analysis was done using SPSS software. Results: Out of 1115 students, 883 responded. 75% of students are willing to take the COVID vaccine. 85% of students are ready to take the vaccine if their head of institution insists them to take. Probability of vaccine non acceptance is higher in lower age group students. Students in the age group of 18–23 are 4.77 times higher risk of not accepting the vaccine compared to students above 23 years. Conclusion: 21–23-year-old age group students are more likely to accept vaccination than lower age group students. MBBS students are less likely to accept than other health-care students.